PENGARUH BEBAN KERJA DAN DISIPLIN TERHADAP KINERJA KARYAWAN PADA PT SANKEN ARGADWIDJA DEPARTEMEN PRODUKSI DISPENSER KABUPATEN TANGERANG - Nur Vicky Ayu Sari; Hamdi Supriadi (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of workload and work discipline on employee performance at PT. Sanken Argadwidja Tangerang Regency dispenser production partially and simultaneously. The method used is a quantitative method. Respondents in this study amounted to 50 people. Data analysis using validity test, reliability test, classical assumption test, regression test, correlation coefficient analysis, determination coefficient analysis and hypothesis test. The results of this study are that Workload has a significant effect on employee performance with a determination value of 50% and in the hypothesis test the T value is obtained 4.064> table 1.677 with a significance value of 0.000 <0.05. Work Discipline has a significant effect on employee performance with a determination coefficient value of 28.6% with the hypothesis test obtaining a t value of 4.387> T table 1.677 with a significance value of 0.000 <0.05. Workload and Work Discipline simultaneously have a significant effect on Employee Performance with the regression equation Y = 24,100 + 0.459 X1 + 0.0.459 X2. The correlation value is 0,615 which means that the independent variable with the dependent variable has a strong relationship. The coefficient of determination value is 37.7%. The hypothesis test obtained an Fcount value of 14.262> Fable 3.09, this is reinforced by a Pvalue of 0.000 <0.05. Thus, Ho is rejected and H3 is accepted.